2021
DOI: 10.1080/26395940.2021.1920467
|View full text |Cite
|
Sign up to set email alerts
|

Pollution risk from Pb towards vegetation growing in and around shooting ranges – a review

Abstract: Commissioned and de-commissioned shooting ranges continue to pose an environmental and human health risk due to the accumulation of toxic Pb emanating from spent munitions. The phytotoxic effects of Pb accumulation in plants include inhibition of root growth and lowering of plant metabolism. The uptake of Pb by plants is directly affected by factors such as plant species and physicochemical properties of the soil. However, scientists and researchers have leveraged on the ability of some plant species to accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 92 publications
(245 reference statements)
0
6
0
Order By: Relevance
“…However, the study of the impact of Pb and other heavy metal contamination on vegetation from intensive hunting ranges are the cornerstones for the control and management of Pb pollution in shooting areas [18,82,83]. This work found that Pb plant concentrations were significantly higher in red-legged partridge shooting areas than in control sites.…”
Section: Discussionmentioning
confidence: 86%
“…However, the study of the impact of Pb and other heavy metal contamination on vegetation from intensive hunting ranges are the cornerstones for the control and management of Pb pollution in shooting areas [18,82,83]. This work found that Pb plant concentrations were significantly higher in red-legged partridge shooting areas than in control sites.…”
Section: Discussionmentioning
confidence: 86%
“… Payne et al. (2013) Dinake et al. (2021) 1, 2 and 3 White-tailed deer ( Odocoileus virginianus ) Pb fragments in abomasum of deer linked to sub-clinical elevated kidney Pb concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The physiochemical characteristics of soil, like soil type, soil pH, cation exchange capacity (CEC), organic matter, and soil texture, affect the Pb uptake by the plant roots [ 35 ]. Among these characteristics, soil pH has a key role in plant uptake by producing protons in roots and resulting in an acidic rhizosphere that favors the dissolution of Pb.…”
Section: Lead In the Soil Environmentmentioning
confidence: 99%
“…Among these characteristics, soil pH has a key role in plant uptake by producing protons in roots and resulting in an acidic rhizosphere that favors the dissolution of Pb. Thus, it has been found that with the decrease in soil pH, Pb absorption also increases and becomes easily accessible to plants [ 35 ]. Additionally, it has been revealed that Pb translocated to shoots when Pb ions cannot precipitate and retain in the cell walls of plants due to the low pH [ 36 ].…”
Section: Lead In the Soil Environmentmentioning
confidence: 99%
See 1 more Smart Citation